Hot Pepper (Capsicum annuum L.) Growth, Fruit Yield, and Quality Using Organic Sources of Nutrients. (15th December 2017) - Castellanos, Javier Z.; Cano-Ríos, Pedro; García-Carrillo, Edgar M.; Olalde-Portugal, V.; Preciado-Rangel, Pablo; Ríos-Plaza, Juan L.; García-Hernández, José L.
ABSTRACT: Many greenhouse-vegetable growers cannot participate in the organic market due to the scarcity of organic fertilizers, which are able both to (a) satisfy the crop's nutritional needs similarly to when using a nutrient solution, and (b) be regarded as biological, ecological, or in general terms "sustainable." Four different fertilization regimes using three different hot pepper genotypes were applied under greenhouse conditions in arid land of Mexico. The three genotypes were of the "Serrano" variety and were obtained from different arid lands in northern Mexico. The entire crop management was 100% organic according to United States organic standards. We found that vermicompost—obtained from the metabolism of Eisenia fetida feed with cow manure plus maize waste—was able to supply the needed nutrients to the cultivars to obtain a growth and yield similar to the plants supplied with nutrient solution. The most productive genotype (Don Diego) showed the following fresh yield values: 1.98, 1.84, 1.24, and 1.11 kg plant −1 for treatments with conventional nutrient solution, vermicompost, solarized cow manure, and solarized poultry manure, respectively. The fertilization with poultry manure resulted in lower values in every growth and yield variable measured. However, this same treatment showed the highest values in ascorbic acid with 328.6 and 327.4 mg 100 mL −1 for genotypes Don Ramón and Don Vicente, respectively. The overall results suggest that organic sources of nutrients may be able to supply the needs of greenhouse hot peppers as alternative for organic farmers. Treatment with vermicompost showed the general best behavior in all of the plants.